Partnerstwo publiczno-prywatne w teorii i w praktyce gospodarczej - Agnieszka Cenkier (Ekonomiczne Problemy Usług, 2015)
Delivery of public services has been proved to be a heavy task for goverments all over the word in numerous ocasions. When cuts in public spendings are necessary, while the needs of the society keep beeing higher and higher, this becomes a real challenge. Public-private partnership appeared to be a good means to bypass shortages in public funds. However experience got in applying it has changed the previous understanding of how it works considerably. In Poland some progress in the field of using public-private partnership has been observed. Actually it is not clear enough why Polish economy couldn’t manage so far to take a chance of public-private partnership like other countries did, but some circumstances can be pointed out.